Tools for the management of the popular political participation: cultural and political resources (Islas, 2022)
ABSTRACT Introduction: The preparation of the people to assume that responsibility rests mainly, in the work of direction that the leaders develop, as managers of participation and socializing agents. This work is developed within the framework of social relations, especially those of leadership and politics. Methods: The political cultural resources for the management of popular political participation are analyzed from an inductive perspective, through approaches: pedagogical, cultural, and linked to science, technology and society. Results: Among the political cultural resources necessary for the management of popular political participation from the management work are: acquired multidimensional knowledge, values, convictions, valuations (meanings), cultural patterns, political position and awareness, personal example, leadership capacity, political behavior and mode of action. Also, resources of this nature are the various methods, mechanisms and means used by the leader in each context of action, among them: the relationship and consultation with the masses, dialogue, persuasion, suggestion and assertive communication. Conclusions: The political cultural resources are the theoretical-methodological tools that make possible the effectiveness of the process in the work of the leaders, in function of contributing to the process of conscientization and training of the people to participate in the construction of a prosperous and sustainable socialism.